Particle induced X-ray emission and Rutherford backscattering spectrometry for testing homogeneity of environmental certified reference material candidates. Issue 6 (3rd May 2021) - Idris, Abubakr M.; Alkhuraiji, Turki S.; Alnajjar, Ahmed O.; Fawy, Khaled F.; Elgorashe, Rafea E. E.; Ebrahim, Ammar M.; Noun, Manale; Srour, Ali; Roumié, Mohamad; El-Zahhar, Adel A.; Ashraf, I. M.
ABSTRACT: Taking advantages of non-destructive techniques, between-bottles homogeneity tests were carried out in term of elemental composition of seven certified reference materials (CRMs) candidates using particle-induced X-ray emission technique (PIXE). A combination of PIXE and RBS techniques (Rutherford backscattering spectrometry) was also used for CRMs candidates having biological matrices. The CRMs candidates have the matrices of soil, sediment, dust, fish muscle, leaves and fruit, which will be certified for some major, minor and trace elements. One batch was produced for each CRM candidate, which included 80 bottles. Between-bottles homogeneity tests were performed for each CRM candidate using seven representative bottles. The repeatability of measurements by PIXE and RBS was examined. The relative standard deviations (RSD) and relative average deviation (RAD) of the elements contents were considered for variability assessment for both repeatability and between-bottles homogeneity. Al, Si and Fe showed good repeatability with RSD and RAD of <4%, while Mg, S, Cl, K, Ca, Mn and Sr showed RSD and RAD in the range of 4–10%. A content of one element in the examined CRMs candidates, with the exception of the date fruit, showed RSD and RAD of <5% indicating good between-bottles homogeneity. For date fruit, the relative error of all elements was <10%, with the exception of Si and Zn, while RAD of S, Cl and K were <10%.